Electronic textbook of machine parts and control of students’ knowledge using a computer (Pedagogy of Higher and Secondary Education, 2012)
Antonenko I. Electronic textbook of machine parts and control of students’ knowledge using a computer.The brought features over of development and use of electronic textbook from the details of machines and checking of knowledge of students of pedagogical institution of higher education system by means of computer in the conditions of the credit-module system.
Keywords: details of machines; electronic textbook; computer testing